The Portuguese schools' evaluation programme: a sociological approach to the participation of social actors - Luísa Veloso; Abrantes, P; Craveiro, D. (Evaluation, 2013)
his article analyses the current Portuguese Schools' Evaluation Programme, implemented since 2006 in all state schools, as a social construction. The article focuses on a particular topic of the external evaluation the participation of social actors in school life, as well as on school principals' perceptions of the process. Our research is based on a content analysis of schools' evaluation reports conducted in three different regions (Lisbon and Tagus Valley, Alentejo and Algarve) and a series of semi-directive interviews with the principals and chairpersons of the General Councils of 20 schools. While it is important to consider the evaluation programme in the light of international political tendencies (e. g. New Public Management), it is also relevant to understand the impact of such policy on schools. We highlight the contributions of this approach to a wider reflection on evaluation processes.